Plataforma computacional para projeto de lente de contato escleral personalizada - Daniel Ferreira Filgueiras (2015)
This paper presents the development and testing of a computational platform to adapt and optimize optical properties of scleral contact lenses using ocular biometric data of patients. The proposal is an alternative to replace the conventional lens prescription method, which consists of time consuming empirical tests. The proposed platform is designed to receive ocular biometric information of patients and desired lens power and, through internal processing, define the physical structure of the scleral contact lens that best fits to requirements. Are provided as outputs the production parameters for the manufacturing laboratory of scleral lens. The computational platform was built using the numerical calculation software Matlab® and dedicated optimization algorithms associated with the software of optical modeling systems Zemax®. The algorithms used to design the scleral contact lens prioritize their optical quality in a reduced computational processing time, through two optimization methods: Genetic Algorithm and Quasi-Newton Broyden, Fletcher, Goldfarb and Shanno (BFGS). This work presents the design, optimization and manufacturing of a scleral lens that best fits a test individual. This paper illustrates the application of the proposed technique in a case study, where it succeeds in designing a scleral lens from ocular biometric data, whose the optical quality obtained is superior to the non-optimized lens. This solution offers convenience to the ophthalmologist at the time of the lens prescription and for the patient a well suited product to your eye with good optical quality.